2020
DOI: 10.1063/5.0006530
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of near surface MOVPE grown InGaAs/InP quantum wells

Abstract: In this work, we study the electron mobility of near surface metal organic vapor phase epitaxy-grown InGaAs quantum wells. We utilize Hall mobility measurements in conjunction with simulations to quantify the surface charge defect density. Buried quantum wells are limited by polar optical phonon scattering at room temperature. In contrast, the quantum wells directly at the surface are limited by remote charge impurity scattering from defects situated at the III–V/oxide interface or inside the oxide, showing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The ALD passivation therefore improves both the mobility and sheet carrier density of near-surface AlInAs/GaInAs twodimensional electron gas (2DEG) channels. Similar findings were recently reported by Södergren et al [41].…”
supporting
confidence: 93%
“…The ALD passivation therefore improves both the mobility and sheet carrier density of near-surface AlInAs/GaInAs twodimensional electron gas (2DEG) channels. Similar findings were recently reported by Södergren et al [41].…”
supporting
confidence: 93%
“…The Hall mobility obtained here is consistent with previous works. [20] It is, however, interesting to note that the mobility is higher for samples with higher In content, which is in line with the fact that InAs has higher electron mobility than GaAs. In Figure 3d, the mean value of the fitted contact resistance, which is positive for all samples, is plotted together with a 95% confidence interval.…”
Section: Resultssupporting
confidence: 53%
“…InGaAs quantum wells, coated with InAlAs and grown on AlGaAsSb buffer layers by the method of molecular beam epitaxy, can achieve room-temperature mobilities that can be used to fabricate Field-effect transistors (FETs) for the performance of DC and RF characteristics [22]. It has been shown that in InGaAs/InP quantum well structure, the mobility increases with depositing a layer of oxide on the surface due to decrease in the number of defects at the interface [23]. In a GaAs/InGaAs QW, the transport of electrons has been analyzed with the application of many-body effects and magnetic field, taking into consideration of both non-phonon and phonon scatterings [24].…”
Section: Introductionmentioning
confidence: 99%